The discomfort of diabetes: three women in front of the mirror, the word and death - Cleves-Valencia, Juan José; Ocampo-Cepeda, Rita Patricia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2018)
This research tackles how has been shaped the relationship of three diabetic women-whose medical treatment includes the use of insulin therapy- with their chronic condition. This relationship is elucidated, fundamentally, taking as a referent point the real, imaginary, symbolic triad propounded by the french psychoanalyst Jacques Lacan. It is a study that questions the modes of relationship established within medical practices around diabetes, as well. In terms of methodology, it opts for a qualitative research through in-depth interviews.